Accountability, Transparency in Financial Management, Abdi Sabda Medan Theological College - Rajagukguk, Desi; Sianturi, Desy Ruth; Bella Simanjuntak; Christopel Tambunan; Patar Nababan; Tetti Manullang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to understand financial management accountability at the Abdi Sabda College of Theology (STT) Medan in 2023. By using a phenomenological approach in qualitative methods, this study reveals the meaning of financial management accountability at this private educational institution. Data was obtained through interviews and observation. The research results show that the financial management of STT Abdi Sabda Medan has met applicable accounting standards, as evidenced by the availability of financial reports as a form of accountability to the Trustees of the STT Abdi Sabda Medan Foundation.